Climatological characteristics of the synoptic changes accompanying South China Sea summer monsoon withdrawal. (30th August 2018) - Hu, Peng; Chen, Wen; Huang, Ruping; Nath, Debashis
Abstract : This manuscript analyses the climatological characteristics (especially the synoptic phenomena and changes) of the South China Sea (SCS) summer monsoon withdrawal (SCSSMW) based on monsoon retreat dates from the National Climate Center of China Meteorological Administration. The SCSSMW is mainly defined as the westerly to easterly shift in the zonal winds due to the westwards intrusion of the western North Pacific (WNP) subtropical high in the northern SCS region. At the low level (850 hPa), the weakening and retreat of the intertropical convergence zone (ITCZ) and rain belt in the SCS–WNP are pertinent, and the southwesterly winds over the north Indian Ocean and the SCS also weaken and retreat. The anomalous anticyclone centred over the northern SCS resembles a Rossby wave response to the reduced precipitation over the SCS and the Philippine Sea. Changes in the upper‐level (200 hPa) circulations include the deceleration of the tropical easterly stream (from the Indo‐China Peninsula to the Arabian Sea) and northerly cross‐equatorial flow (around the equatorial eastern Indian Ocean and Maritime Continent). At the mid‐level (500 hPa), the ascending centre moves equatorwards, shifting from the northern to the southern SCS. There appears an anomalous vertical circulation cell (descending/ascending in the northern/southern SCS), which links the anomalous horizontal circulation through the Sverdrup balance. In addition, the upper‐level divergent centre is shifted southeastwards, as is the generating centre of tropical cyclones. Moreover, an anomalous convergent centre over Taiwan Island is prominent in the upper level. The time series of several atmospheric variables (e.g., zonal wind, precipitation, convection) also exhibited abrupt changes during the SCSSMW. The reasons for not simultaneous retreat of monsoonal westerlies and rainy season in the SCS are also explored. Abstract : The climatological characteristics of the South China Sea summer monsoon withdrawal (SCSSMW) show a weakening and retreat of the monsoon trough and rain belt in the SCS and western North Pacific (WNP). And the southwesterly winds over the North Indian Ocean and the SCS also weaken and retreat as shown in the image. The anomalous anticyclone centred over the northern SCS resembles a Rossby wave response to the reduced precipitation over the SCS and the Philippine Sea.